Inventarisasi Jenis Gulma di Areal Perkebunan Karet (Hevea brasiliensis) Pada Ketinggian Tempat Yang Berbeda di Negeri Liang Kecamatan Teluk Elpaputih Kabupaten Maluku Tengah - Dilyan N Ramlan; Johan Riry; Vilma L Tanasale (Universitas Pattimura, 2019)
The purpose of this study was to analyze the types of dominant weeds in rubber plantation areas at altitudes of 4 m above sea level (asl) and 104 m asl and to find differences in the types of weeds in the rubber plantation areas at an altitude of 4 m asl and 104 m asl. This research conducted in Negeri Liang, Teluk Elpaputih District, Central Maluku Regency. This research used a